2018
DOI: 10.1111/eff.12437
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeomorphic factors drive differences in otolith morphology in fish from the NuSalween River

Abstract: Understanding the relationship between intraspecific phenotypic variation and habitat is fundamentally important to ecology and evolution. However, it is largely unknown whether the environment drives the morphological variation in riverine fish otoliths, which are potential phenotypic markers. In this study, we investigated morphological variations in the otoliths of an endemic Chinese fish (Schizothorax nukiangensis Tsao) collected from seven sites with varying environmental gradients along the Nu‐Salween Ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…On the contrary, the complicated dynamics most naturally should force the phenotype specialisation towards lacustrine lifestyle in small-numbered isolated populations. The parallel origin of lacustrine morphotype was reported for charrs (Kristjansson, Leblanc, Skulason, Snorrason, & Noakes, 2018;Kristjansson et al, 2012) and other fish taxa (Ding et al, 2019;Franssen, Harris, Clark, Schaefer, & Stewart, 2013;Kaeuffer, Peichel, Bolnick, & Hendry, 2012); a similar morphotypes have evolved from independent populations after colonising similar environments. Herewith, we found the prevalence of unique morphological and anatomical features in six populations derived from common S. malma.…”
Section: Discussionsupporting
confidence: 59%
“…On the contrary, the complicated dynamics most naturally should force the phenotype specialisation towards lacustrine lifestyle in small-numbered isolated populations. The parallel origin of lacustrine morphotype was reported for charrs (Kristjansson, Leblanc, Skulason, Snorrason, & Noakes, 2018;Kristjansson et al, 2012) and other fish taxa (Ding et al, 2019;Franssen, Harris, Clark, Schaefer, & Stewart, 2013;Kaeuffer, Peichel, Bolnick, & Hendry, 2012); a similar morphotypes have evolved from independent populations after colonising similar environments. Herewith, we found the prevalence of unique morphological and anatomical features in six populations derived from common S. malma.…”
Section: Discussionsupporting
confidence: 59%
“…Previously L. Ding and coauthors (Ding et al, 2019) found that the variability of the otoliths of Schizothorax nukiangensis Tsao, 1964 could be related to the river dynamics driven by its fall. They showed the otoliths of S. nukiangensis sampled in different habitats had a significantly different morphology, in particular they reported an increase of their length.…”
Section: Discussionmentioning
confidence: 99%
“…S. nukiangensis is an endemic species in the Nujiang River. It inhabits cold and fast-flowing water and has the widest distribution area, with an elevation range from 700 to 3800 m (Ding et al, 2019). It grows slowly and can live up to 22 years with a maximum total length >75 cm (Ding et al, 2019).…”
Section: Study Speciesmentioning
confidence: 99%